STRUCTURAL, SEMANTIC, AND FUNCTIONAL ASPECTS OF IMPERSONAL SENTENCES IN ENGLISH (Ideal Journal of Multidisciplinary Research, 2026)
Impersonal sentences represent a key grammatical phenomenon in English, enabling speakers to describe general states, natural phenomena, and situations where the agent is unknown or irrelevant. Unlike personal sentences, impersonal constructions do not focus on a concrete subject but emphasize events, conditions, or generalized information. This article provides a detailed analysis of the structural, semantic, and functional characteristics of impersonal sentences in English. Special attention is given to constructions with the dummy subject it, existential there sentences, and passive forms omitting the agent. The study examines stylistic, pragmatic, and communicative functions, demonstrating how impersonal sentences contribute to objectivity, generalization, and formal expression in both written and spoken discourse. Findings suggest that understanding impersonal constructions is essential for mastering English syntax and achieving stylistic precision in academic, literary, and everyday communication.
Keywords: impersonal sentence, dummy subject, existential construction, passive voice, English grammar, syntactic structure, communicative function, stylistics.